Regulation of T Cell Activities in Rheumatoid Arthritis by the Novel Fusion Protein IgD-Fc-Ig - Zhang, Jing; Hu, Xiaoxi; Dong, Xiaojie; Chen, Wensheng; Zhang, Lingling; Chang, Yan; Wu, Yujing; Wei, Wei (Frontiers in Immunology, 2020)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation and T cell hyper-activation. Emerging evidence has shown that the stimulation of immunoglobulin D (IgD) induces T cell activation and may contribute to diseases pathogenesis. In this study, the sIgD concentrations were positively associated with disease activity score in 28 joints (DAS28) and anti-cyclic citrullinated peptide (anti-CCP) in RA. We demonstrated that IgD-Fc-Ig (composed of human IgD Fc domain and IgG1 Fc domain, obtained through prokaryotic protein expression and chromatography purification) effectively inhibited the activation and proliferation of T cells in healthy controls and PBMCs in RA patients stimulated by IgD, recovered the Th17/Treg cell subset balance, and downregulated p-Lck and p-ZAP70 expression. Moreover, in vivo, IgD-Fc-Ig decreased the swollen joint counts and arthritis indices in mice with collagen-induced arthritis (CIA), and ameliorated histopathological changes in joint and spleen tissue. It also downregulated thymocyte proliferation and reduced the percentage of helper T cells (Th) and CD154+ T cells, reversed the imbalance of Th1/Th2 and Th17/Treg cell subsets, reduced cytokine and chemokine levels, and inhibited p-Lck and p-ZAP70 expression. Our data suggest that IgD-Fc-Ig fusion protein regulates T cell activity in RA. These findings have potential implications for IgD-targeted strategies to treat IgD-associated RA.